Theoretical and methodological prerequisites for improving the system of physical culture and sports events for persons with disabilities in a pedagogical university - Fokin, A.M.; Ovchinnikov, V.P.; Shelkova, L.N.; Shevtsov, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate the necessity of improving the system of physical culture and sports events for students with disabilities in a pedagogical university and to empirically prove the effectiveness of the proposed recommendations. Methods and structure of the study. A special questionnaire was developed for the study. The survey involved 300 students of the Herzen State Pedagogical University of Russia from the 1st to the 4th year, across all areas of training, assigned by medical examination results to special medical group “B” (SMG-B) with exemption from practical classes in the hall (therapeutic exercise or theoretical classes), male and female (45/55), aged 18–24 years. The students were divided into an experimental (EG) and a control (CG) group of 150 persons in each sample. Results and conclusions. The results of the empirical study demonstrated that the introduction of physical culture and sports events for students with disabilities in a pedagogical university nearly doubles their involvement in physical education and sport. In connection with the proof of the effectiveness of the proposed measures, their practical application is recommended for all students with psychophysical developmental features.